The Impact of Mesenchymal Stem Cells on Differentiation of Hematopoietic Stem Cells - Saleh, Mahshid (Adv Pharm Bull, 2015)
Bone marrow microenvironment contains cellular and acellular compartments. The cellular compartment includes hematopoietic stem cells, mesenchymal stem cells and some other stromal cell types, while the acellular compartment is composed of scaffold proteins known as the extra cellular matrix. Direct cell-cell contact as well as cytokines secreted by mesenchymal stem cells during coculture of hematopoietic stem cells and mesenchymal stem cells play a critical role in hematopoiesis, and determines the fate of hematopoietic stem cells. Several studies have demonstrated the impact of mesenchymal stem cells on self-renewal, expansion, proliferation and differentiation of hematopoietic stem cells in vitro, which have shown different and contradictory results. In this paper, we will investigate the effect of mesenchymal stem cells on differentiation of hematopoietic stem cells in vitro.